Surgical Treatment of Intraductal Papillary Neoplasm of the Bile Duct: A Report of Two Cases and Review of the Literature - Li, Binjie; Liu, Zhiqiang; Meng, Zhuo; Li, Mingyang; Tian, Weijun; Liu, Quanyan (Frontiers in Oncology, 2022)
Intraductal papillary neoplasm of the bile duct (IPNB) is a rare bile duct tumor characterized by intraductal papillary or villous neoplasms covered by neoplastic epithelium with fine fibrovascular stalks in the dilated bile ducts [1]. Its true etiology remains unknown. Herein, we report two cases of IPNB that underwent surgical resection. The first case was a 66-year-old male who complained of upper abdominal pain for three years. We found obstruction of the common bile duct and dilation of the intrahepatic and extrahepatic bile ducts after MRCP. Laparoscopic hepatic segmentectomy (S2, S3, S4), resection of the common bile duct, cholecystectomy, and hepaticojejunostomy were performed. The second case was a 67-year-old male with asymptomatic dilation of the intrahepatic duct. The patient underwent robot-assisted laparoscopic hepatic segmentectomy (S5, S6, S7, S8), resection of the common bile duct, hepaticojejunostomy and cholecystectomy.